Remdesivir and Its Combination With Repurposed Drugs as COVID-19 Therapeutics - Chatterjee, Bhaswati; Thakur, Suman S. (Frontiers in Immunology, 2022)
The SARS-CoV-2 virus needs multiple copies for its multiplication using an enzyme RNA-dependent RNA polymerase (RdRp). Remdesivir inhibits viral RdRp and controls the multiplication of the virus and protects the patients. However, the treatment of COVID-19 with remdesivir involves adverse effects. Many ongoing clinical trials are exploring the potential of the combination of remdesivir with repurposed drugs by targeting multiple targets of virus and host human simultaneously. Better results were obtained by the combination of remdesivir-baricitinib treatment for COVID-19 compared to the treatment with remdesivir. Notably, the recovery from COVID-19 was found to be eight days less by the treatment with remdesivir-baricitinib combination as compared to remdesivir treatment. Further, the mortality rate by the treatment with remdesivir-baricitinib combination was less compared to only remdesivir treatment. Remdesivir targets the SARS-CoV-2 enzyme while baricitinib targets the host human enzyme. Simultaneously, both the compounds remdesivir-baricitinib as a combination are inhibiting their target viral RdRp and human janus kinase respectively. Ongoing trials for the combination of drugs will suggest in the future whether they may reduce the recovery time, reduce the mortality rate and improve the patient clinical status for the noninvasive ventilation. In the future, simultaneously targeting virus replication enzymes and host human kinases may be the strategy for SARS-CoV-2 therapeutics.